2019
DOI: 10.1016/j.molmed.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory TGF-β Signaling in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is an inflammation-induced and chemotherapy-resistant cancer. Dysregulated signaling in the transforming growth factor beta (TGF-b) pathway plays a central role in inflammation, fibrogenesis, and immunomodulation in the HCC microenvironment. This review dissects the genetic landscape of the TGF-b superfamily genes in HCC and discusses the essential effects of this pathway on the tumor immune microenvironment. We highlight the TGF-b signature as a potential biomarker for identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
150
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(152 citation statements)
references
References 83 publications
2
150
0
Order By: Relevance
“…Protein expression of BMP-4 and BMP-7 was upregulated in HBV-related human cirrhosis/HCC samples, and the overexpression of BMP-4 and BMP-7 increased cell viability and enhanced cell migration in HCC cell-lines. [22] Moreover, Chen and coworkers reported that gene amplification and increased gene expression of BMP-5 were significant in HCC samples [66]. This is in agreement with our finding that BMP-5 may contribute to the fibrogenic and tumorigenic processes in the liver.…”
Section: Discussionsupporting
confidence: 92%
“…Protein expression of BMP-4 and BMP-7 was upregulated in HBV-related human cirrhosis/HCC samples, and the overexpression of BMP-4 and BMP-7 increased cell viability and enhanced cell migration in HCC cell-lines. [22] Moreover, Chen and coworkers reported that gene amplification and increased gene expression of BMP-5 were significant in HCC samples [66]. This is in agreement with our finding that BMP-5 may contribute to the fibrogenic and tumorigenic processes in the liver.…”
Section: Discussionsupporting
confidence: 92%
“…103,104 Recent studies have demonstrated that TGF-B participates in tumorigenesis. 105,106 When the liver progenitor cells are stimulated by TGF-β, they are transformed into tumor-initiating cells as evidenced by TGF-β-induced changes in CD133 and CD90 expression ( Figure 3). 105 In comparison with the extrinsic effects, the intrinsic actions of TGF-β signaling are largely observed in highly invasive tumor conditions ( Figure 3).…”
Section: In the Regulation Of Hccmentioning
confidence: 99%
“…CNOT7 expression was increased, whereas STAT1 expression was decreased in HCC tumor tissues. TGF‐β1 is a powerful immune suppressor secreted from cancer cells of many cancer types, including HCC [11–13,27]. Plasma concentration of TGF‐β1 was positively correlated with the degree of tumor progression in patients with lung or colorectal cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma concentration of TGF‐β1 was positively correlated with the degree of tumor progression in patients with lung or colorectal cancer [28]. TGF‐β1 inhibits cytokine secretion and cytotoxicity of NK cells [15–18,27]. NK cell function was impaired, which had been widely observed in patients with advanced cancer [29–31].…”
Section: Discussionmentioning
confidence: 99%